Bacterial and fungal bloodstream infections in solid organ transplant recipients: results from a Danish cohort with nationwide follow-up. (March 2022) - Møller, Dina Leth; Sørensen, Søren Schwartz; Perch, Michael; Gustafsson, Finn; Rezahosseini, Omid; Knudsen, Andreas Dehlbæk; Scheike, Thomas; Knudsen, Jenny Dahl; Lundgren, Jens; Rasmussen, Allan; Nielsen, Susanne Dam
Abstract: Objectives: Bloodstream infections (BSI) are prevalent after solid organ transplantation (SOT). In this study, we aimed to investigate the incidence and risk factors for BSI in the first 5 years post-transplantation. Methods: The study included 1322 SOT (kidney, liver, lung and heart) recipients transplanted from 2010 to 2017 with a total of 5616 years of follow-up. Clinical characteristics and microbiology were obtained from the Centre of Excellence for Personalized Medicine of Infectious Complications in Immune Deficiency (PERSIMUNE) data repository with nationwide follow-up. Incidence was investigated in the different SOT groups. Risk factors associated with BSI were assed in the combined group in time-updated multivariable Cox regressions. Results: The cumulative incidence of first BSI in the first 5 years post-transplantation differed in the SOT groups with a lower incidence in heart transplant recipients than in the other SOT groups (heart: 4.4%, CI 0.0–9.7%, vs. kidney: 24.6%, CI 20.9–28.2%, liver: 24.7%, CI 19.4–29.9%, and lung: 19.6%, CI 14.5–24.8%, p <0.001). Age above 55 years (HR 1.71, CI 1.2–2.4, p=0.002) and higher Charlson comorbidity index score (HR per unit increase: 1.25, CI 1.1–1.4, p<0.001) at transplantation, current cytomegalovirus (CMV) infection (HR 4.5, CI 2.6–7.9, p<0.001) and current leucopenia (HR 13.3, CI 3.7–47.9, p<0.001) were all associated with an increased risk of BSI. Conclusion: In SOT recipients, the incidence of BSI differed with the type of transplanted organ. Risk of BSI was higher in older recipients and in recipients with comorbidity, current CMV infection or leucopenia. Thus, increased attention towards BSI in recipients with these characteristics is warranted.